Entrepreneurial ecosystems in an interconnected world: emergence, governance and digitalization - Ricarda B. Bouncken; Sascha Kraus (Review of Managerial Science, 2021)
Achieving and sustaining growth depends on the effective work of multiple and interconnected actors—such as e.g. governments, the private sector, society, universities, entrepreneurs and many others—who build an ecosystem, i.e. a social and economic environment for innovative and entrepreneurial endeavors. The underlying idea is that firms do not just compete with each other through well-developed stand-alone strategies to achieve advantages over their rivals, uniquely relying on their own resources, knowledge, and capabilities, but rather base their business models on shared resources, network externalities, knowledge spill-overs, local endowments, and governmental support. This introductory article offers a wide array of topics, methods and fields of application within the field of entrepreneurial ecosystems as well as a theorizing about potential fruitful future areas of research within the field, concentrating on legitimation and identification processes in ecosystems, possibly culminating towards a meta-identity of the ecosystem.
Keywords: M1; M10; M19; M20; 650; Entrepreneurship; Entrepreneurial; Innovation; Ecosystems; Digitalization